Regulating Ecocide in Indonesia Based on the Precautionary Principle - Ferdiantoro, Seto; Chanifah, Nur; Qurbani, Indah Dwi (International Journal of Business, Law, and Education, 2025)
Ecocide, as a massive and far-reaching environmental crime, is gaining increasing attention in various countries including Indonesia. However, Indonesian national law has not explicitly regulated ecocide as a stand-alone crime. In this context, administrative law theory, particularly the Precautionary Principle, plays an important role in formulating legal policies that are responsive to environmental threats. This research uses a normative juridical method with a statutory approach and a conceptual approach. This article analyzes the legal construction of ecocide in Indonesia using the Precautionary Principle theory as an analytical knife to explore whether the current legal policy is sufficient in preventing and overcoming environmental crimes. The results of the research show that there are still many laws and regulations that were born without paying attention to the precautionary principle. This analysis concludes with recommendations for the establishment of more comprehensive ecocide regulations to provide more effective legal protection for the environment.